PRECISION AGRICULTURE: use of drones to map agricultural areas - Ribeiro, Gabriel Felipe Vieira; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2022)
This work covers the technologies in which they carried out a study that involves precision agriculture, where we look for references that address the importance of this innovation for increasing the productivity of crops, using procedures, in the handling of drones, that do not attack nature. And this work aims to provide a brief overview of the process that includes precision agriculture with drones and environmental licensing. The concept of georeferencing, the use of drones in rural properties and mapping with the same were also presented. To this end, bibliographic research of a qualitative and descriptive-exploratory nature was carried out. It is concluded that the use of drones is an extremely economical and innovative tool, which provides agility to services and is very useful when working in areas of difficult access.